2000
DOI: 10.1053/rmed.1999.0769
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the safety and efficacy of moxifloxacin (BAY 12-8039) and cefuroxime axetil in the treatment of acute bacterial sinusitis in adults

Abstract: The aim of this multicentre, randomized study was to compare the efficacy and safety of moxifloxacin (BAY 12-8039), a new 8-methoxy fluoroquinolone, with that of cefuroxime axetil for the treatment of acute bacterial sinusitis in adults. Diagnosis was made on a range of clinical signs and symptoms combined with radiology and microbiology. A 400 mg dose of moxifloxacin was administered once daily for 7 days to 242 patients and 250 mg twice daily of cefuroxime axetil was administered to 251 patients for 10 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 22 publications
4
51
0
3
Order By: Relevance
“…44 However, evidence for moxifloxacin and telithromycin suggests that a shorter course of 5-7 days is clinically and/or bacteriologically equivalent to a 10-day course. 45,46 Recent studies have also shown that bacteriological eradication occurs within 72 hours with moxifloxacin (400 mg once daily) or with high-dose, short-course levofloxacin (750 mg once daily for five days). 47,48 This higher dose of levofloxacin improves the PK/PD profile of the agent and in a comparative trial of this dose versus levofloxacin 500mg once daily for 10 days, clinical and microbiological efficacy was found to be similar.…”
Section: Duration Of Antibiotic Treatment For Absmentioning
confidence: 99%
“…44 However, evidence for moxifloxacin and telithromycin suggests that a shorter course of 5-7 days is clinically and/or bacteriologically equivalent to a 10-day course. 45,46 Recent studies have also shown that bacteriological eradication occurs within 72 hours with moxifloxacin (400 mg once daily) or with high-dose, short-course levofloxacin (750 mg once daily for five days). 47,48 This higher dose of levofloxacin improves the PK/PD profile of the agent and in a comparative trial of this dose versus levofloxacin 500mg once daily for 10 days, clinical and microbiological efficacy was found to be similar.…”
Section: Duration Of Antibiotic Treatment For Absmentioning
confidence: 99%
“…Two additional trials eligible for inclusion were detected after a secondary search on the Scopus database, but no additional trials were identified in the Cochrane Central Register of Controlled Trials. A total of 11 trials [21][22][23][24][25][26][27][28][29][30][31] were included in the meta-analysis ( Figure 1). The 2 reviewers independently reached the same conclusions regarding studies to be included.…”
Section: Selected Trialsmentioning
confidence: 99%
“…In addition to the treatments being compared in these studies, adjunctive medications for symptomatic relief, mostly decongestants, antihistamines and analgesics, were permitted in 8 of the trials. 22,[24][25][26][27][28][29][30] Two of these trials reported the percentage of patients using such medications: 76% in one study 28 and 83.5% in the other.…”
Section: Characteristics Of the Selected Trialsmentioning
confidence: 99%
“…L'efficacia clinica e la tollerabilità della moxifloxacina nella CAP, nelle AECB e nelle ABS sono state studiate su un numero elevato di pazienti, nel corso di diversi trial multicentrici controllati, nazionali e internazionali, strutturati nella maggior parte come studi in doppio cieco [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118].…”
Section: Efficacia Clinica E Batteriologica Nelle Infezioni Acute Delunclassified